Evaluation of cardiotoxicity five years after 2D planned, non-simulated, radiation therapy for left breast cancer - Kyriaki Pistevou-Gompaki; Apostolos Hatzitolios; Nikos Eleftheriadis; Evaggelos Boultoukas; George Ntaios; et al (Dove Medical Press, 2008)
Kyriaki Pistevou-Gompaki1, Apostolos Hatzitolios2, Nikos Eleftheriadis2, Evaggelos Boultoukas2, George Ntaios2, Ioannis Andronikidis2, Ioannis Tzitzikas11Department of Radiation Oncology; 2First Propedeutic Department of Internal Medicine, AHEPA Hospital, Aristotle University, Thessaloniki, GreeceIntroduction: Radiation treatment has been associated with radiation induced cardiotoxicity, especially with older, long-outdated, techniques. Such complications include pericarditis, myocardial fibrosis, valvular injury, ischemic heart disease, and myocardial infarction.Aim: To assess the effect of outdated breast radiation therapy (RT) – using a diagnostic CT scanner in the absence of a CT simulator – on cardiac function in women with stage II left breast cancer.Patients and Methods: Sixty-two women under 65 with stage II left breast cancer who received post-operative RT using a diagnostic computed tomography scanner were studied between 1997 and 2001. Participants underwent a clinical interview, ECG, and echocardiography before and 6 months and 5 years after RT.Results: There was no serious cardiotoxicity at 6 months and 5 years after radiotherapy. A 23% increase in hypertensive patients, and a slight decrease (2.3%) in ejection fraction was observed after 5 years, with 3 patients (5%) developing abnormalities. Two patients presented abnormal electrocardiographic findings within 6 months of RT.Conclusion: Our study showed that RT for left breast cancer was not associated with significant alteration in heart morbidity or mortality within 5 years of treatment, despite the lack of a simulator.Keywords: radiotherapy, breast cancer, cardiotoxicity, acute myocardial infraction, ischemic heart disease